Citrus Foliar Fungal Diseases - Megan M. Dewdney; Jamie D. Yates (EDIS, 2009)
PP261, a 2-page illustrated identification sheet by Megan M. Dewdney and Jamie D. Yates, can be used to identify four fungal diseases in citrus: Alternaria Brown Spot, Citrus Scab, Greasy Spot, and Melanose. Published by the UF Department of Plant Pathology, March 2009.